Minimum data sets in women’s health: Opportunities and challenges explored within the context of developing a core outcome set for pre-eclampsia - Duffy, J (2018)
Future pre-eclampsia research should ultimately improve patient care. For this to be possible, randomised trials must select, collect, and report outcomes that genuinely reflect the perspectives of key stakeholders, including healthcare professionals, researchers, and women with pre-eclampsia. The objective of this study was to develop a core outcome set for pre-eclampsia, along with standardised definitions, to ensure outcomes and outcome measures are consistently selected, collected, and reported across future primary research, secondary research, and clinical practice guidelines. A long list of 116 potential core outcomes was developed by undertaking a systematic review of 79 published pre-eclampsia trials and thematic analysis of 30 in-depth interviews of women with lived experience of pre-eclampsia. The long list of potential core outcomes was entered into a modified Delphi method. Four hundred and thirty-two participants, including 281 healthcare professionals, 41 researchers, and 110 patients, representing 31 high-income countries and 25 low- and middle-income countries participated in a three-round Delphi survey. One hundred and fifty-nine participants (37%) withdrew. Forty-seven consensus outcomes were identified and entered into a modified nominal group technique. Eleven healthcare professionals, two researchers, and three women with lived experience of pre-eclampsia prioritised 14 maternal, four fetal, and four neonatal core outcomes. A long list of 86 potential definitions were identified by reviewing four formal definition development initiatives, eight international and national guidelines, 11 Cochrane systematic reviews, and 79 pre-eclampsia trials. During a consensus development conference involving ten healthcare professionals and three researchers, consensus definitions were successfully developed for all core outcomes. Embedding the core outcome set within future pre-eclampsia research could make a profound contribution to advancing the usefulness of research to inform clinical practice, enhance patient care, and improve maternal and offspring outcomes.